Penamaan Unik Menu Makanan pada Kafe dan Warung di Kota Lhokseumawe (Kajian Semantik) - Maulidawati Maulidawati; Syahriandi Syahriandi; Monadia Monadia (Institut Agama Islam Negeri Curup, 2024)
Naming food menus is an important aspect of marketing strategies for cafes and food stalls. Unique naming can attract consumer attention. This research explores the basics of the unique naming of food menus used by cafes and stalls in Lhokseumawe City. This research uses qualitative methods to analyze data collected through direct observation and interviews with business owners, reinforced with documentation and notes. The results of the research showed that there is a cause or basis for the naming used, namely (1) imitation of sounds with 2 data, (2) mention of parts with 3 data, (3) mention of distinctive characteristics with 11 data, (4) inventor and maker with 1 data, (5) place of origin with 5 data, (6) material with 2 data, (7) similarity with 3 data, (8) shortening with 2 data, and (9) new naming with 1 data. The basis or the reason for the unique naming of this food menu is dominated by the mention of the unique characteristics, namely 11 pieces of data. The practical implication of this research is to help business owners develop creative and different menu naming strategies to create their own identity and attract customers' attention.